Sexual harassment among nurses at workplace in a tertiary hospital of Kathmandu - Thapa, Himali; Sharma, Sharada (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Sexual harassment is a form of discrimination that includes unwelcome and inappropriate sexual advances, requests for sexual favors, or verbal, non-verbal, or physical conduct of a sexual nature. The research aimed to identify the different forms of sexual harassment experienced by nurses at work place.Methods: A descriptive cross-sectional study was conducted in a tertiary hospital of Kathmandu from January to June 2025. Purposive sampling technique was used for the selection of hospital. To ensure representation from all wards, a disproportionate stratified random sampling technique was used to select nurses for the study. Data was collected from 150 nurses through a structured self-administered questionnaire. Collected data was entered and analyzed in SPSS; descriptive statistics were used.Results: The findings revealed that 39.4% nurses reported experiencing verbal sexual harassment, 25.4% experienced non-verbal sexual harassment, 15.9% encountered physical sexual harassment, and 9.3% faced cyber sexual harassment during their lifetime. In addition, 20.7% of nurses reported being subjected to persistent staring while 14.7% reported feeling awkward due to sexually inappropriate comments at the workplace.  Of total, 5.3% faced the sending of explicit messages or images via electronic platforms. Notably, 24.7% of the perpetrators were relatives of patients or clients.Conclusions: The study concluded that nearly two fifths of the nurses reported experiencing verbal sexual harassment, one-fourth experienced non-verbal sexual harassment, and nearly one in ten nurses faced cyber sexual harassment at workplace during their lifetime. The nurses recommend for establishing clear policies and protocols to prevent and control sexual harassment.